Forecasting Short-Run Variation in Labor Market Activity - David, Martin; Otsuki, Toshiyuki (The Review of Economics and Statistics, 1968)
EVERY adult consciously or unconsciously determines the extent to which he supplies labor for economic activities. Every business determines the extent to which it wishes to increase its work force by new hiring or the extent to which it wishes to reduce its work force by layoffs. The outcome of these decisions is recorded in a monthly tally of the employed (E), unemployed (U), new hires (h), layoffs and quits (s),' and the number of adults outside the labor force (N). As a first step towards understanding the supply and demand relationships that determine the flows of new hires and separations and the stock of unemployed, the authors have examined the Markov matrix A, that determines transitions between the state of Employment, Et, Unemployment of less than one month's duration Uot, Unemployment of more than one month's duration Ult, and non-labor force participation Nt. By definition